Pemberdayaan Masyarakat Melalui Digital Marketing UMKM Toko Oleh-Oleh Arta Berkah di Desa Simpar Kecamatan Bandar Kabupaten Batang - Choirunnisa Choirunnisa; Hendy Setiawan (Hippocampus: Jurnal Pengabdian Kepada Masyarakat, 2023)
The development of science and technology, such as social media, has shown extraordinary progress, especially in the economic sector. This is supported by the development of communication technology in selling products, which initially carried out manual marketing through door to door, shifting to the digital marketing era. Digital Marketing as a marketing strategy that is carried out through several digital media such as blogs, websites, Adwords, Instagram, Twitter and Facebook. The method used in this community service uses a participatory real approach in the form of outreach and assistance, in this activity it is carried out through two stages, namely preparation and socialization. The results of this study in general, MSME actors in Simpar Village do not understand scientifically in conducting marketing either via the internet. The use of social media in the utilization of internet marketing is still minimal so that community empowerment activities in digital marketing are urgently needed. This of course raises awareness that the importance of a strategy in marketing such as expanding reach in improving the character, image, impression of a product itself.